Puyo Runa : Imagery and Power in Modern Amazonia - Whitten, Norman E., Jr. (Norman Earl), 1937- (Book collections on Project MUSE., 2008)
The Andean nation of Ecuador derives much of its revenue from petroleum that is extracted from its vast Upper Amazonian rain forest, which is home to ten indigenous nationalities. Norman E. Whitten Jr. and Dorothea Scott Whitten have lived among and studied one such people, the Canelos Quichua, for nearly forty years. In Puyo Runa, they present a trenchant ethnography of history, ecology, imagery, and cosmology to focus on shamans, ceramic artists, myth, ritual, and political engagements. Canelos Quichua are active participants in national politics, including large-scale movements for social justice for Andean and Amazonian people. Puyo Runa offers readers exceptional insight into this cultural world, revealing its intricacies and embedded humanisms.